2013
DOI: 10.1556/jba.2.2013.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise addiction in Spanish athletes: Investigation of the roles of gender, social context and level of involvement

Abstract: Background and aims: In nomothetic research exercise addiction is studied on the basis of symptoms which are most often linked to exercise volume. However, other factors may also affect individuals' susceptibility to the disorder. The aim of this research was to examine the influence of gender, social context (team or individual sport), and level of athletic training on symptoms of exercise addiction. Methods: Two groups of university athletes – sport- (n = 57) and non-sport orientation (n = 90) – and a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 14 publications
12
59
5
6
Order By: Relevance
“…In accordance with past research, competitive exercisers in this study scored higher on REA than non‐competitive exercisers. As indicated earlier, it was argued that these differences could be attributed to possibly different interpretations of the items assessing REA by competitive versus non‐competitive exercisers…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with past research, competitive exercisers in this study scored higher on REA than non‐competitive exercisers. As indicated earlier, it was argued that these differences could be attributed to possibly different interpretations of the items assessing REA by competitive versus non‐competitive exercisers…”
Section: Discussionsupporting
confidence: 92%
“…Increases in REA were positively predicted by gender (being female) and by type of sport (doing team sports). For gender, these findings do not agree with previous studies (Modoio et al 2011;Szabo et al 2013) and a recent literature review (Dumitru et al 2018). However, Weik and Hale (2009) showed that depending on the instruments used, either men or women may score higher on REA.…”
Section: Predictors Of Risk For Exercise Addiction and Passion Changescontrasting
confidence: 75%
“…Men are more at risk of primary exercise addiction and women secondary exercise addiction. 3,4 The focus of this article will be on primary exercise addiction.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%